Photonic Scheme for the Generation of Background-Free Phase-Coded Microwave Pulses and Dual-Chirp Microwave Waveforms - Guangyi Li; Difei Shi; Zhiyao Jia; Lu Wang; Ming Li; Ning Hua Zhu; Wei Li (IEEE Photonics Journal)
We propose a photonic scheme to generate binary phase-coded microwave pulses and dual-chirp microwave waveforms without baseband-modulated signals (background noise) based on a dual-polarization dual-drive Mach-Zehnder modulator (DP-DDMZM) which contains x-DDMZM and y-DDMZM at two different polarization states. A radio frequency (RF) signal from a microwave source is transferred into two differential RF signals and employed into one arm of x-DDMZM and one arm of y-DDMZM, while a baseband signal from an arbitrary waveform generator is divided by an electronic coupler and then driven into the two other arms of DP-DDMZM. By adjusting the phase differences between the x-DDMZM and the y-DDMZM, binary phase-coded pulses and dual-chirp signals without baseband-modulated signals are generated. The proposed scheme can eliminate the interference caused by baseband-modulated signals, and satisfy different radar applications for different frequency bands. Experimental results show that phase-coded signals at 15 GHz with the bit rates of 1 Gb/s and 2 Gb/s and dual-chirp signals at 10 GHz and 15 GHz with the time durations of 0.5 μs are successfully generated. The reported scheme is well analyzed in theory and verified by experiment.